2022
DOI: 10.15584/ejcem.2022.3.11
|View full text |Cite
|
Sign up to set email alerts
|

The role of the hematological inflammatory index and systemic immuno-inflammation index in acute cholecystitis

Abstract: Introduction and aim. Acute cholecystitis is one of the most common hepatobiliary emergencies. We aimed to investigate the role of the initial hematological inflammatory index and systemic immuno-inflammation index in predicting short-term mortality in patients with acute cholecystitis. Material and methods. This study with a retrospective observational design was conducted at the emergency department of a tertiary teaching hospital. Patients admitted to our clinic between June 15, 2021, and March 15, 2022, ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 0 publications
1
4
0
Order By: Relevance
“… 33 It has also demonstrated associations with short-term outcomes and advanced forms of acute cholecystitis. 13 , 34 Within our study, we observed that the cutoff value of SII for differentiating between ACC and CCC was 896.8, and for predicting MS-ACC it was >1261. These findings indicated the potential clinical utility value of SII in assessing the severity and prognosis of acute cholecystitis.…”
Section: Discussionsupporting
confidence: 52%
“… 33 It has also demonstrated associations with short-term outcomes and advanced forms of acute cholecystitis. 13 , 34 Within our study, we observed that the cutoff value of SII for differentiating between ACC and CCC was 896.8, and for predicting MS-ACC it was >1261. These findings indicated the potential clinical utility value of SII in assessing the severity and prognosis of acute cholecystitis.…”
Section: Discussionsupporting
confidence: 52%
“…For example, SII was noted to be significantly higher in the non-survivor patients with acute cholecystitis than in the survivors in a Turkish study. [15] A high level of SII is an independent risk factor for short survival of patients with metastatic and unresectable pancreatic cancer. Patients with a high level of the inflammatory markers SII, neutrophil-to-lymphocyte count neutrophil/lymphocyte ratio (NLR), and the platelet-to-lymphocyte count, may be more prone to early liver metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the discrepancies concerning the cut-off values, we believe that NLR is an important parameter in the diagnosis of AA and in differentiating between complicated and uncomplicated cases. SII, a new-generation comprehensive systemic inflammatory index, has been reported to be a prognostic marker in some malignant diseases, autoimmune diseases, such as Behçet's disease and ankylosing spondylitis, abdominal infections, and many other diseases and conditions, from low-level infection to sepsis 19,20,[26][27][28][29] . It has been suggested that SII is a more successful marker than PLR and NLR in showing inflammation and immune response [20][21][22][23][24][25][26][27] .…”
Section: Discussionmentioning
confidence: 99%
“…The literature has reported that parameters such as red blood cell distribution width, the neutrophil/lymphocyte ratio (NLR), and the platelet/lymphocyte ratio (PLR) are important indicators of systemic inflammation and can be used to determine its prognosis 8,[15][16][17] . The systemic immune-inflammatory index (SII) is a new inflammatory index developed to simultaneously reveal the inflammatory and immune status of patients through the calculation of neutrophil count × platelet count / lymphocyte count 18,19 . SII has been shown to be an accurate marker for inflammation and immune response 20 .…”
Section: Introductionmentioning
confidence: 99%